RESPON MASYARAKAT RW 019 KELURAHAN TUAH KARYA TERHADAP DIDIRIKANNYA TEMPAT HIBURAN CHROMATIC FAMILLY KARAOKE DI KECAMATAN TUAH MADANI KOTA PEKANBARU - Sri Rahayu Ningsih; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to determine the response of the people in RW 019 Exodus Tuah Karya to the establishment of the Chromatic Family Karaoke entertainment venue. The response is seen from three aspects, namely Cognitive Response, Affective Response and Conative Response, while to see the factors that influence the formation of the response can be seen from three factors, namely internal factors, living environment, culture. This research was conducted on people living in RW 019, Tuah Karya sub-district. To get the right results, the author uses descriptive quantitative methods which are presented in tabular form and explained in detail with a total sample of 79 respondents. The results of this study indicate that the public's response to the establishment of chromatic family karaoke is high or negative. Both from cognitive, affective and conative responses. That's because there are factors that influence the formation of responses, from factors that influence the formation of responses, internal factors, living environment, culture, in this study are classified as high, meaning that the presence of these factors can affect the formation of a person's response to something. For this reason, capital owners need to pay more attention to the location and place where the place of business will be established, especially karaoke entertainment venues, because not everyone thinks that the place is said to be good as a place of entertainment. Keywords: Response, RW019 Community, Chromatic Family Karaoke